Long is the way and hard : one hundred years of the National Association for the Advancement of Colored People (NAACP) - Verney, Kevern, 1960-; Sartain, Lee (Fayetteville : University of Arkansas Press, 2009)
Kevern Verney is associate head of the Department of English and History at Edge Hill University, England, and the author of The Debate on Black Civil Rights in America.
The NAACP in historiographical perspective / Kevern Verney and Lee Sartain -- "All shadows are dark" : Walter White, racial identity, and national politics / Simon Topping -- In Harlem and Hollywood : the NAACP's cultural campaigns, 1910-1950 / Jenny Woodley -- "A gigantic battle to win men's minds" : the NAACP's public relations department and post-Brown propaganda / George Lewis -- Leading from the back : Roy Wilikins's leadership of the NAACP / Yvonne Ryan -- Uneasy alliance : the NAACP and Martin Luther King / Peter J. Ling -- The NAACP and the challenges of 1960s radicalism / Simon Hall -- The Falls Church Colored Citizens Protective League and the establishment of Virginia's first rural branch of the NAACP / Beverly Bunch-Lyons and Nakeina Douglas -- "To hope till hope creates" : the NAACP in Alabama, 1913-1945 / Kevern Verney -- "It's worth one dollar to get rid of us" : middle-class persistence and the NAACP in Louisiana, 1915-1945 / Lee Sartain -- "in no event shall a Negro be eligible" : the NAACP takes on the Texas all-white primary, 1923-1944 / Charles L. Zelden -- Tensions in the relationship between local and national NAACP branches : the example of Detroit, 1919-1941 / Patrick Flack -- The Chicago NAACP : a century of challenge, triumph, and inertia / Christopher Robert Reed -- The NAACP in California, 1914-1950 / Jonathan Watson -- "Your work is the most important, but without branches there can be no national work" : Cleveland's branch of the NAACP, 1929-1968 / Andrew M. Fearnley -- "They say ... New York is not worth a d -- to them" : the NAACP in Arkansas, 1918-1971 / John A. Kirk.
Not distributed; available at Arkansas State Library.
Includes bibliographical references (pages 247-297) and index.
eBooks on EBSCOhost
Keywords: National Association for the Advancement of Colored People -- History -- 20th century; National Association for the Advancement of Colored People; African Americans -- Civil rights -- History -- 20th century; Civil rights movements -- United States -- History -- 20th century; African Americans -- Politics and government -- 20th century; United States -- Race relations; Noirs américains -- Droits -- Histoire -- 20e siècle.; Mouvements des droits de l'homme -- États-Unis -- Histoire -- 20e siècle.; Noirs américains -- Politique et gouvernement -- 20e siècle.; États-Unis -- Relations raciales; HISTORY -- United States -- State & Local -- General; POLITICAL SCIENCE -- Civil Rights; African Americans -- Civil rights; African Americans -- Politics and government; Civil rights movements; Race relations; United States; 1900-1999; History